1991
DOI: 10.1088/0026-1394/28/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Comparateur d'étalons de masse: une étude expérimentale des coefficients de corrélation des paramètres mesurés

Abstract: The mass comparator for primary standards of the INM is a high level metrological set. Recently, its balance has been put into a thermally isolated and airtight chamber and this has led us to engage in an experimental study concerning the independence of the measured parameters. This study has revealed that the independence hypothesis must be rejected. The different correlation coefficients have been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…Consequently, it is necessary to clean them in order to obtain a mass value which is as stable and reproducible as possible. Many studies have been made of the influence of different cleaning methods on mass standards made from platinum-iridium, superalloys or stainless steels [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, it is necessary to clean them in order to obtain a mass value which is as stable and reproducible as possible. Many studies have been made of the influence of different cleaning methods on mass standards made from platinum-iridium, superalloys or stainless steels [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A gravimetric study [17,18] of the effect of cleaning kilograms 07 and 09 with alcohols showed that this method caused a considerable short-term instability of mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A quaternary cobalt-based alloy provided by Aubert & Duval, Alacrite XSH, has also been studied at the LNE-INM (Institut National de Métrologie) for the realization of transfer mass standard [12,13]. The chemical composition of these cobalt-based alloys is reported in table 1.…”
Section: Materials Of the Studymentioning
confidence: 99%
“…Therefore, as the functional relationship of most of the quantities appearing in (4.13) to the "basic" quantities depends on the experimental method adopted, any further modelling in terms of these "basic" quantities would compromise generality (see e.g. [19] for a specific case). However, in order to gain a deeper understanding of the various contributory sources, we will now specialize (4.13) according to some of the methods most commonly adopted and discuss the properties of the various terms of (4.13).…”
Section: The Construction Of $Y In Its General Formmentioning
confidence: 99%